2015
DOI: 10.1038/srep11811
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution NMR characterization of low abundance oligomers of amyloid-β without purification

Abstract: Alzheimer’s disease is characterized by the misfolding and self-assembly of the amyloidogenic protein amyloid-β (Aβ). The aggregation of Aβ leads to diverse oligomeric states, each of which may be potential targets for intervention. Obtaining insight into Aβ oligomers at the atomic level has been a major challenge to most techniques. Here, we use magic angle spinning recoupling 1H-1H NMR experiments to overcome many of these limitations. Using 1H-1H dipolar couplings as a NMR spectral filter to remove both hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
91
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 54 publications
11
91
0
1
Order By: Relevance
“…60 Previous ssNMR studies have shown α-helical structures of Amylin and not cross-β structure. 61,62 Recent ssNMR studies presented unstructured Aβ oligomers 63 and Amylin oligomers that form large micelles, 64 which may be a general phenomenon for natively unstructured Amylin. We did not apply these α-helical and the unstructured amylin, or the unstructured Aβ oligomers in the current study, because of the lack of the PDB coordinates.…”
Section: Resultsmentioning
confidence: 99%
“…60 Previous ssNMR studies have shown α-helical structures of Amylin and not cross-β structure. 61,62 Recent ssNMR studies presented unstructured Aβ oligomers 63 and Amylin oligomers that form large micelles, 64 which may be a general phenomenon for natively unstructured Amylin. We did not apply these α-helical and the unstructured amylin, or the unstructured Aβ oligomers in the current study, because of the lack of the PDB coordinates.…”
Section: Resultsmentioning
confidence: 99%
“…Solid-state NMR has proven to be a powerful tool for detailed structural characterization of non-crystalline amyloid at atomic resolution. 4355 However, structural analyses of the tertiary β-structure within this 127-residue TTR amyloid are a daunting task. We recently demonstrated that specific labeling schemes, which generate isolated 13 CO- 13 Cα dipolar-coupled spin pairs in the native β-sheets (Figure 5a), are of great use for probing the native β-sheet structure in amyloid state.…”
Section: Resultsmentioning
confidence: 99%
“…They characterized low‐abundance oligomers of Aβ in the presence of other monomers and fibrils, without purification. With the aid of radio‐frequency‐driven 2D 1 H, 1 H experiments based on dipolar recoupling, a 5 to 10 nm small oligomeric species of Aβ40 was identified as a dynamic and disordered intermediate along the fibril pathway …”
Section: Experimental Studiesmentioning
confidence: 99%